مقاصدِ شریعت کی روشنی میں طبی اخلاقیات کا عملی نفاذ: Practical Implementation of Medical Ethics in Light of the Objectives of Sharia’h (Al-Qamar, 2021)
This article explores the practical relevance of medical ethics within the framework of the higher objectives of Shariah (Maqāṣid al-Sharī‘ah). Medical ethics guide physicians in adopting morally responsible conduct, particularly in an era marked by materialism, diminishing spiritual values, and the inability of modern medicine to address several emerging ethical challenges. In Islam, the ethical foundation of medical practice is deeply rooted in five essential objectives: protection of religion, life, progeny, intellect, and wealth. Any medical procedure that upholds these objectives is considered ethical, whereas actions that violate them are deemed impermissible. Given that the medical profession is directly connected with safeguarding human life, physicians bear significant responsibilities including compassion, patience, confidentiality, social welfare, professional competence, and sincere service. The rising prevalence of diseases such as AIDS, COVID-19, and other infectious illnesses has increased the need for qualified medical practitioners. Therefore, the proper application of medical ethics is crucial for preventing negligence and ensuring professional accountability. This study highlights the importance of integrating Shariah-based ethical principles into contemporary medical issues, particularly in light of rapid technological advancements, social changes, and newly emerging biomedical challenges.
Keywords: Maqasid al-Shariah, Medical Ethics, Islamic Bioethics, Professional Accountability, Contemporary Medical Challenges